Xenon as a Component of Anesthetic Maintenance for Early Activation of Patients after Myocardial Revascularization - Ye. V. Dzybinskaya; O. V. Stepanova; I. A. Kozlov (Общая реаниматология, 2009)
Objective: to make a complex analysis of the efficacy of xenon as the major agent in maintaining anesthesia during early activation of patients operated on under extracorporeal circulation for coronary heart disease. Subjects and methods. Forty-two patients aged 59±3 years were examined. A total of 3±0.2 coronary arteries were shunted. General anesthesia was induced and maintained by propofol and fentanyl under extracorporeal circulation. Anesthesia was maintained by xenon inhalation in the preperfusion and postperfusion periods. General anesthesia was combined with high (Th3—Th4) epidural anesthesia in 10 cases. Results. During xenon inhalation, the central hemodynamic parameters were maximally steady-state both before and after extracorporeal circulation. The coronary perfusion conditions estimated from the coronary perfusion gradients were stable. The study of the conditions for coronary perfusion and the values of myocardial demand showed the persistence of their balance (r=0.55—0.83; p<0.05). With the use of epidural anesthesia as a component of maintenance, there was a two-fold increase (p<0.05) in the use of sympathomimetic agents. Lower Pa02 after initiation of xenon inhalation and, accordingly, decreased Fi02 were not associated with worse Pa02/Fi02 and increased intrapulmonary blood shunting; there were no changes in blood oxygen-transport function. Emergence from anesthesia occurred 9±1.2 min after the termination of xenon delivery and failed to be accelerated when epidural anesthesia was applied. The latter could reduce the inhaled concentration of xenon from 59.2±0.5 to 51.5±0.5% (p<0.05) and the dosage of fentanyl from 2.9±0.15 to 2.1±0.26 ^g/kg/hr <p<0.°5). The use of xenon as a basic anesthetic has prospects during early activation after myocardial revascularization under extracorporeal circulation. The advantage of xenon is the absence of negative effects on central hemodynamics and the presence of conditions for coronary perfusion in patients with coronary heart disease. This mode of maintenance provides not only an effective anesthetic protection, but also emergence from anesthesia in the range of 3 to 25 minutes after the end of operations, which allows one to make an early activation in the operating suite in more than 90% of cases. Key words: xenon, xenon anesthesia, early activation after surgery under extracorporeal circulation, anesthesia in patients with coronary heart disease.